Control of Entry into Meiosis of Germ Cells Precursors in Chickens (Global Journal of Science Frontier Research, 2015)
This paper describes experiments on the induction of sex reversal in chickens by estrogen inhibitors (letrozole, tamoxifen), demethylating agent 5-azacytidine and retinoic acid (RA). Particular attention is paid to control entry into meiosis of germ cells. The obtained data indicates a partial overlap control of somatic and gametic sex.
Keywords: sex reversal; aromatase; estrogen; 5-azacytidine; retinoic acid; meiosis; germ cells; chicken